Influence of Ta Additive into Cu84-xAl13Ni3(wt%) Shape Memory Alloy Produced by Induction Melting - Mohammed, Safar Saeed; Kok, Mediha; Qader, Ibrahim Nazem; Kanca, M. Sait; Ercan, Ercan; Dagdelen, Fethi; Aydogdu, Yildirim (Springer Int Publ Ag, 2020)
Thermal and morphological analysis of shape memory alloys is one of the important branches of research to obtain new characteristics. In this study, low amounts of tantalum were added into CuAlNi alloy. The alloy was produced with the induction melting method. The phase transformation of the alloys was characterized by DSC and electrical resistivity for an equal range of temperatures. The alloys showed high-temperature phase transformations. Although the alpha phase existed in all cases, its peak intensity in the XRD result was significantly decreased by adding Ta. The matrixes showed fine martensite plates with beta(1)', and there were also coarse martensite plates with gamma '. Crystallite sizes and Vickers microhardness of the alloys were decreased with increasing tantalum additive. The Cu84Al12Ni3Ta wt% alloy recorded maximum elastic energy and Gibbs free energy.
Keywords: CuAlNiTa; Shape memory alloy; Induction melting method